(untitled) (LEARNing Landscapes, 2013)
The ongoing emphasis on early years education in Ontario provided a rich context for this research project, commissioned by The Learning Partnership (TLP), to evaluate a new provincial project called FACES (Family and Community Engagement Strategy). This initiative seeks to extend and enhance community-based, multi-agency partnerships that support young children and their families in successful transitions to school. Interview data from individuals and focus groups suggest re-thinking early childhood education practices to include innovative multi-agency, community-based partnerships. "Seven Keys to Success" in building multi-agency partnerships emerged from the data providing direction for educators and policy makers.